Deconstructing the molecular architecture of olfactory areas using proteomics. Issue 12 (20th June 2016) - Lachén‐Montes, Mercedes; Fernández‐Irigoyen, Joaquín; Santamaría, Enrique
Abstract : The anatomy of the olfactory system is highly complex, comprising a system of olfactory receptors, pathways for the transmission of olfactory information, and structures for the recognition, discrimination, and memorization of odors. During the last years, proteomics has emerged as a large‐scale comprehensive approach to characterize and quantify specific olfactory‐related proteomes in different biological conditions such as olfactory learning, neurodegeneration, and ageing between others. The current work reviews recent applications of proteomics to olfaction with particular focus on quantitative proteome profiling studies performed on olfactory areas from laboratory animal models as well as proteomic characterizations performed on specific brain structures and fluids involved in human smell. Finally, we will also discuss the potential application of proteomics to study global proteome dynamics and posttranslationally modified proteomes in order to unravel cell‐signaling networks that occur from peripheral structures to olfactory cortical areas during odor processing.